The male germline of angiosperms: repertoire of an inconspicuous but important cell lineage - Russell, Scott D.; Jones, Daniel S. (Frontiers in Plant Science, 2015)
The male germ line of flowering plants constitutes a specialized lineage of diminutive cells initiated by an asymmetric division of the initial microspore cell that sequesters the generative cell from the pollen vegetative cell. The generative cell subsequently divides to form the two male gametes (non-motile sperm cells) that fuse with the two female gametophyte target cells (egg and central cells) to form the zygote and endosperm. Although these male gametes can be as little as 1/800th of the volume of their female counterpart, they encode a highly distinctive and rich transcriptome, translate proteins, and display a novel suite of gamete-distinctive control elements that create a unique chromatin environment in the male lineage. Sperm-expressed transcripts also include a high proportion of transposable element-related sequences that may be targets of non-coding RNA including miRNA and silencing elements from peripheral cells. The number of sperm-encoded transcripts is somewhat fewer than the number present in the egg cell, but are remarkably distinct compared to other cell types according to principal component and other analyses. The molecular role of the male germ lineage cells is just beginning to be understood and appears more complex than originally anticipated.